A Characterization of Utilitarism Without the Transitivity Axiom - Vincenzo Denicolò (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1996)
We show that d'Aspremont and gevers' (1977) characterization of utilitarism can be strenghened in the following way. First, the condition of transitivity of the social preference relation is dropped and the Anonymity condition is slightly strengtened. (Our Anonymity condition is weaker than the combination of transitivityand d'Aspremont and Gever's Anonimity condition). Second, the Strong Pareto Principle is the Weak Pareto Principle.
Keywords: 330